Comparative study of the relevance of equity financing in European SMEs - Wieczorek-Kosmala, Monika; Błach, Joanna; Trzęsiok, Joanna (Journal of Business Economics and Management, 2020)
This paper contributes to the academic debate on the pecking order theory and SMEs equity financing, in this equity financing gap. In order to address this problem, this study relies on the empirical design that is driven by the premises of the pecking order theory and distinguishes between the relevance of internal funds vs. external equity. The main aim of this study is to investigate whether the relevance of equity financing for European SMEs is driven by the country-specifics (captured by the clusters of the EU countries) and whether there are any other factors that may potentially explain the relevance of internal funds or external equity, with respect to SMEs performance and characteristics. For that purposes the SAFE survey data were used to run non-parametric and correlations analysis. The results have clearly indicated that there are statistically significant differences between the clusters of the EU countries (if we differentiate between core and peripheral EU countries in particular). It was also found that there is no unified pattern of the associations between the relevance of equity financing and SMEs performance and characteristics, thus these associations seem to be influenced by the country-specifics as well.